THE ROLE OF CRITICAL THINKING IN ACADEMIC PAPERS (Ustozlar uchun, 2026)
Critical thinking plays a fundamental role in the development and quality of academic papers. It enables researchers and students to analyze information objectively, evaluate evidence, and construct logical arguments based on reliable sources. In academic writing, critical thinking helps authors avoid bias, identify weaknesses in existing studies, and present well-supported conclusions. Moreover, it encourages creativity and independent thought, which are essential for solving complex academic problems. The process of critical analysis also improves the organization and clarity of research papers by helping writers connect ideas systematically and coherently. In higher education, the ability to think critically is considered one of the most important academic skills because it supports effective decision-making, problem-solving, and scholarly discussion. This article examines the significance of critical thinking in academic writing, its influence on research quality, and the methods through which students can develop critical thinking abilities. The study concludes that strong critical thinking skills contribute to more persuasive, analytical, and academically valuable papers, making them an essential component of successful academic research and professional development.